Tauhid Kepada Allah dan Fondasi Utama Ajaran Islam dan Pentingnya dalam Kehidupan Sehari-Hari - Andini, Intan Rosari; Indra, Nayla Zafira; Ash-Shadiqin, Hasbi; Berutu, Nazwa Felinda; Wismanto, Wismanto (STAI Denpasar Bali, 2024)
Tawhid is a fundamental concept in Islamic teachings that teaches the oneness of Allah SWT and is the basis of all deeds. A correct understanding of tawhid is very important to maintain faith and safety in this world and the hereafter. This study aims to understand the basic concept of tawhid, analyze the types of tawhid, examine the relationship between types of tawhid, and identify the importance of instilling the values ​​of tawhid in life, especially at an early age. The method used in this study is a qualitative approach with a descriptive-analytical method, which is a library research. Data were collected through literature reviews from various sources relevant to the theme of tawhid. The results of the study found that tawhid can be divided into three interrelated levels, namely Rububiyah tawhid, Uluhiyah or ubudiyah tawhid, and Asma' wa Sifat tawhid. Instilling the values ​​of tawhid from an early age is very important to form a child's personality that is strong in faith. A correct understanding and practice of tawhid will lead individuals to safety in this world and the hereafter. With a strong foundation of tawhid, a person can survive various challenges that can shake his faith.